Um olhar para as professoras que ensinam matemáticas nas Escolas do Campo em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
In the current context, we consider that training processes directed to the reality of teachers and students, are essential to promote meaningful and critical education, focused on an education that strives for equity. In this direction, the study in question reflects on the teaching of Mathematics in rural schools, especially the practices of teachers who graduated from the Specialization Course in Rural Education – Federal University of Amazonas (Ufam). In this way, articulated to our experiences and knowledge sharing aimed at establishing approximations between the students' prior knowledge and the contents approached by the teachers in the classroom, in the Research and Research Group on Investigative Practices in Mathematics Education (GEPIMat) / Ufam / CNPq, we asked in this research: In what terms do the processes of continuing education contribute to the practices of teachers who teach mathematics in schools in the countryside? In this sense, we aim to understand the practices of teachers with the teaching of Mathematics in rural schools, based on the processes of continuing education. With a qualitative approach, the research in question is guided by a Case Study, having as participants, two teachers who work with the teaching of Mathematics in schools in the countryside of the city of Manaus-AM. Thus, we adopted as instruments for the collection and analysis of information, observation, notes in the field diary, audiovisual recordings and the use of training courses, based on the narratives of the teachers participating in the research, in addition to the bibliographic analysis, based on Course Completion Works (TCC) developed by the research participants, in the Specialization Course in Rural Education, with an emphasis on pedagogical practices, offered by the Rural Education Program / Ufam. As for the results found, they signaled that the teachers consider that the continuing education corroborates so that they reflect and review their practices with the teaching of Mathematics in the Amazonian field.
A look at the teachers who teach mathematics at Schools in the Countryside in Manaus
Keywords: Processos formativos; Matemática - Estudo e ensino; Matemática - Ensino do campo; Práticas investigativas; Desenvolvimento profissional; CIÊNCIAS HUMANAS; Formação continuada de professores; Educação do Campo; Ensino de Matemática